Clinical Characteristics of Pediatric Thoracolumbar Spinal Injuries: A Retrospective Study - Syed Aamir Shah, Saeed Ullah, Musadique Latif Memon, Badar Uddin Ujjan, Muhammad Mujahid Sharif, Amjad Ali Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the clinical characteristics of pediatric thoracolumbar spinal injuries Study design: A retrospective study Place and Duration:This study was conducted at Pakistan Institute of Medical Sciences Islamabad from Jan 2021 to Jan 2022 Methodology:An analysis of pediatric thoracolumbar (TL) injuries was conducted to determine the epidemiology, risk factors, mechanisms, patterns, and management of pediatric TL injuries. A plain radiograph (anteroposterior and lateral view) was taken on all patients for diagnosis. In the case of surgical intervention or doubtful skeletal abnormalities observed on plain radiographs, thin-slice computerized tomography (CT) scans were obtained. In patients with neurological deficits or those who were scheduled for surgical intervention, magnetic resonance imaging (MRI) was performed. Results:A total of 90 children were treated at our institute for TL spine injuries, representing 2% of all spine injuries. Males predominate (3:1) with a mean age of 15.9 plus 3.2 years (range: 2–18 years). Falling from a height was the most common mode of injury. Most children (71.1%) sustained injuries after falling from height, 18/90 (20%) after a motor vehicle accident, and the rest after a heavy object fell over their neck. A total of 27.8% of the patients (the majority) had Grade A injuries. The most common spinal level injured was the lumbar spine (53.3%), and fractures accounted for 93.3% of all injuries. A total of 18/90 (20%) children underwent surgical fixation. There were 21 children available for follow-up, of which 13 (62%) were ambulant. Conclusion:The lumbar area is most affected by TL injuries, which are uncommon and most often occur in youth older than 10 years. When necessary, a surgical fusion of the affected vertebrae is a secure and reliable procedure. Keywords: Pediatrics, epidemiology, spine, thoracolumbar, injury